Contributions of African livestock production systems to greenhouse gas emissions and global warming in the face of climate change - Chagunda, M.G.G.; Etchu, K.A.; Tirimba, K.; Okeyo Mwai, Ally (Springer, 2025)
Greenhouse gases (GHG) have the ability to trap radiant energy from the sun in the atmosphere. The accumulation of GHGs in the atmosphere significantly contributes to climate change. Methane is 21 times more potent than CO2 as a greenhouse gas (GHG), however, this is one area where there is a lack of robust data to reflect the amount of GHG different breeds of cattle in Africa produce per day. With an increasing global population placing pressure on land resources, coupled with environmental degradation of existing agricultural land, climate change mitigation and adaptation becomes even a more urgent issue to deal with. Livestock contributes to approximately 15% of global methane (CH4) emissions and 65% of global nitrous oxide (N2O) emissions, contributing to an estimated 8–11% of global anthropogenic GHG emissions. The production of GHG from ruminants and their impact on climate change are a major concern worldwide. Although the amounts of GHG from African livestock systems may not be as huge as from other production systems in the world, the inefficiencies in African livestock production systems are a call for concern and deserve quantification. Increasing the efficiency of ruminant production is not only vital in reducing the GHG intensity, but also important for food production to meet increasing demands. Strategies to reduce GHG emissions should include the effects of different feeding systems, the level of intensification and genetics/breeding for reduced GHG emissions. Increasing productivity per animal, that is, efficiency, will reduce GHG emissions per kg of livestock product that is needed to improve livestock production without compromising the environment.